Mechanism of Action and Development of Resistance to a New Amidino Penicillin - Matsuhashi, Sachiko (1974)
The mechanism of killing of Escherichia coli by a novel beta-lactam antibiotic, an amidino penicillin, has been investigated. This compound converts E. coli to relatively stable spherical forms at low concentration. However, the amidino penicillin caused no alteration in any of those parameters of peptidoglycan synthesis which can be studied. Above 10 μg of the antibiotic per ml the cells began to lyse, and a second mode of killing appeared. Mutants resistant to the amidino penicillin were isolated and several were studied in detail. Three mutant phenotypes were distinguished: (i) spherical shape and hypersensitive to lysis by either amidino penicillin or ampicillin; (ii) spherical shape and normally sensitive to lysis; (iii) rod shape, converted to viable spheres by amidino penicillin and normally sensitive to lysis.